The needs of disabled fans must not be ignored when sports stadiums reopen to spectators - Penfold, C.; Kitchin, P.; Darby, P. (LSE European Politics and Policy (EUROPP) Blog, 2021)
Most professional sport in Europe has taken place in empty stadiums since the start of the Covid-19 pandemic. However, with the proposed return of spectators upon us, Connor Penfold, Paul Kitchin and Paul Darby arguethe sports industry must facilitate a disability-inclusive restart for spectator sports. Drawing on a recent study, theyoutline a series of recommendations that could be used by stadium operators to ensure the pandemic does not leadto further neglect of the needs and rights of disabled people in the context of sport.